Hospitalizations for respiratory syncytial virus (RSV) in Sicily from 2008 to 2021: clinical features and predictors of severity - Anna Condemi; Domenico Marrali; Chiara Albano; Giulia Linares; Valeria Garbo; Giovanni Boncori; Laura Venuti; Antonio Cascio; Claudia Colomba (Italian Journal of Pediatrics)
Abstract Background Respiratory syncytial virus (RSV) is the leading cause of bronchiolitis, resulting in 3.6 million hospitalizations for acute lower respiratory tract infections and 101,400 deaths in children under 5 years of age worldwide each year. In Europe, the estimated incidence of RSV-related hospitalizations in infants is 1.8%. We describe the incidence of RSV infection in patients hospitalized in Sicily (Italy) between 2008 and 2021, examine the clinical-epidemiological characteristics of RSV-positive patients, and assess comorbidities associated with illness severity. Methods All data were retrospectively collected from standard hospital discharge records (HDRs). Significant factors from the univariate analysis were included in a multivariate logistic regression using the stepwise forward selection method to calculate adjusted odds ratios (aORs) and identify independent risk factors for ICU admission. Results Collectively, within the study time frame, 4,485 hospital admissions were RSV-related, 271 patients (6%) were admitted to the ICU, and eight deceased (0.2%). The majority of hospitalized patients (86%) were infants (up to 1 year old), 16.5% were newborns (<28 days), and 10.1% were in the 1–4-year-old group. Several predictors of ICU admission, including neonatal sepsis, neonatal respiratory distress, and younger age (in months), were identified through multivariate logistic regression analysis. Conclusions RSV-associated pathologies are important causes of hospitalization in Sicily, and young age (particularly 0–3 months) and comorbidities, including nutritional and metabolic disorders (with a stronger effect in the pediatric subgroup) and congenital heart diseases, are important outcome predictors. However, considering that RSV-related diseases continue to require hospitalizations in healthy children and adults, it is important to continue monitoring RSV-related hospitalizations through updated epidemiological studies, which can guide the implementation of existing preventive strategies and inform the cost‒benefit analysis of new ones.